The Application of System Administration Service (Case Study Cihampelas Village Office Kab. Bandung Barat) - Meilani Anggraeni; Mamay Syani; Ade Yuliana (Journal of Innovation Information Technology and Application (JINITA), 2021)
Correspondence administration service activities in the Cihampelas Village Office, West Bandung Regency are still manual with submission forms, approval processes and data recapitulation that have not been stored properly. Time and location constraints and services that often cannot be resolved in one day are problems for people who need fast services. These problems need to be handled quickly to improve excellent service for the local community, so based on the results of interviews with the manager, an application is needed to simplify the letter-making process. The system development method used to make this software uses the Prototype method with stages arranged starting from the requirements collection which contains the stages in the needs analysis, followed by design to testing with the black box testing method. The application is made based on a website using the Laravel framework, MySQL as the database. Based on the results of testing the satisfaction level of application usability through the User Acceptance Test (UAT), the percentage results were 87% of the total 25 user respondents and 3 admin respondents, which concluded that the application built had fulfilled system functionality and was running according to the requirements of the user